Fragmenting markets and quality change in New Zealand foods: empirical analysis with a Rotterdam model - Mohammed Khaled; Vhari McWha; Ralph Lattimore (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2004)
Very little is known about changes in the demand characteristics of food in New Zealand. As far as we can determine, there has never been a complete disaggregated food demand model estimated for New Zealand. The object of this paper is to update these estimates using more recent data to see whether there are grounds for believing that the structural changes that occurred primarily during the last two decades are having effects on the magnitude of food demand elasticities in New Zealand. To this end, a Rotterdam food demand system is estimated using time series data. The results indicate that over the last 20 years, household consumption has increased for fruit and vegetables, poultry, food eaten away from home, and sweet products, drinks and other foods. Fish, poultry, meat, farm products, cereals and meals away from home are all more price elastic than earlier estimates.
Keywords: 330; Lebensmittel; Produktqualität; Konsumentenverhalten; Nachfragesystem; Neuseeland